Postpartum airway responsiveness and exacerbation of asthma during pregnancy – a pilot study - Ali Z; Nilas L; Ulrik CS (Journal of Asthma and Allergy, 2017)
Zarqa Ali,1 Lisbeth Nilas,2,3 Charlotte Suppli Ulrik1,3 1Department of Pulmonary Medicine, 2Department of Gynaecology and Obstetrics, Hvidovre Hospital, Hvidovre, 3Institute of Clinical Medicine, University of Copenhagen, Copenhagen, Denmark Background: Airway responsiveness and inflammation are associated with the clinical manifestations of asthma and the response to pharmacological therapy.Objective: To investigate if airway responsiveness and inflammatory characteristics are related to asthma exacerbations during pregnancy.Materials and methods: In women with asthma who were prescribed controller medication and monitored closely during pregnancy, the risk of exacerbations was analyzed in relation to postpartum measures of fractional exhaled nitric oxide (FENO), skin prick test reactivity, static and dynamic lung volumes, diffusing capacity for carbon monoxide, bronchial responsiveness to inhaled mannitol, and inflammatory characteristics in induced sputum. Obtained data were analyzed in relation to exacerbation status during pregnancy. The PD15 is defined as the cumulative administered dose causing a 15% decline in forced expiratory volume in the first second (FEV1). Results: Fifty women (mean age ± standard deviation of 32±5 years) were enrolled over an 11-month period and examined on average 4 months postpartum. During pregnancy, 13 women had a total of 16 exacerbations (8 mild and 8 severe). Women with asthma exacerbation during pregnancy had more pronounced airway responsiveness to inhaled mannitol (geometric mean PD15 82 vs 171 mg, p=0.04) and were less likely to be atopic (62% vs 86%, respectively; p=0.04) than the non-exacerbators. No statistically significant difference was found between the 2 groups of women with regard to type of airway inflammation in sputum and fractional exhaled nitric oxide (FENO).Conclusion: More pronounced airway hyperresponsiveness together with nonatopic status appears to characterize women at high risk of exacerbation of asthma during pregnancy. Keywords: asthma, inflammation, pregnancy